2002
DOI: 10.1088/1367-2630/4/1/382
|View full text |Cite
|
Sign up to set email alerts
|

Ground to satellite secure key exchange using quantum cryptography

Abstract: Abstract. We examine the possibility of secure key exchange between a ground station and a low earth orbit satellite using the technique of quantum cryptography. The study suggests there are no technical obstacles to building a system that could exchange keys at kilobaud rates between a metre diameter telescope on the ground and a satellite with a 10 cm diameter lightweight telescope.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
145
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 231 publications
(146 citation statements)
references
References 18 publications
0
145
0
1
Order By: Relevance
“…Finally, our scheme should find applications in the forthcoming experiments on long-distance satellite-based QC [3][4][5][6] . There, apart from misalignments, other issues may impose serious obstacles too, such as precise satellite laser-tracking, collection efficiencies, or finite-size effects (for QKD).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Finally, our scheme should find applications in the forthcoming experiments on long-distance satellite-based QC [3][4][5][6] . There, apart from misalignments, other issues may impose serious obstacles too, such as precise satellite laser-tracking, collection efficiencies, or finite-size effects (for QKD).…”
Section: Discussionmentioning
confidence: 96%
“…This is due to the fact that photons, known as so-called 'flying qubits' , are easy to transport from one location to another 1 . Photonic free-space QC has been demonstrated for distances of hundreds of kilometers 2 , a progress that could soon lead to satellite-based long-distance QC [3][4][5][6] . However, standard approaches to QC, for example, the one based on encoding qubits into the polarization of photons, require that all users involved have knowledge of a shared reference frame.…”
mentioning
confidence: 99%
“…This will enforce larger effective transmitter apertures in the regime of 10 cm [116] and even better pointing accuracy. However, in this demonstration, a major challenge was to decouple the optical system, both passively using shock mounts and actively with the FPA, from the vibrating body of the aircraft, which is not necessary to that extent on board a satellite.…”
Section: Classical Subsystemmentioning
confidence: 99%
“…Hughes et al (2002) described experiments over a distance of 10 km at daylight and at night, and Kurtsiefer et al (2002) demonstrated the possibility of globally spanning networks. Studies regarding QKD between a terrestrial station and an orbit satellite have been conducted by Rarity et al (2002) and Pfennigbauer & Leeb (2003). Experimental implementations covering a distance of about 144 km have been reported by Schmitt-Manderbach et al (2007).…”
Section: Outlook: Towards Mobile and Ad-hoc Qkd Networkmentioning
confidence: 99%